Investigation of diltiazem metabolism in fish using a hybrid quadrupole/orbital trap mass spectrometer - Koba, Olga; Steinbach, Christoph; Kroupová, Hana Kocour; Grabicová, Kateřina; Randák, Tomáš; Grabic, Roman (Rapid communications in mass spectrometry, 2016)
RATIONALE: Diltiazem, a calcium channel blocker drug, is widespread in the environment because of its incomplete elimination during water treatment. It can cause negative effects on aquatic organisms; thus, a rapid and sensitive liquid chromatography/mass spectrometry (LC/MS) method to detect its presence was developed. Our approach is based on accurate mass measurements using a hybrid quadrupole-orbital trap mass spectrometer that was used to measure diltiazem and its metabolites in fish tissue. METHODS: Blood plasma, muscle, liver, and kidney tissues of rainbow trout (Oncorhynchus mykiss), exposed for 42 days to 30 μg L(-1) diltiazem, were used for the method development. No metabolite standards were required to identify the diltiazem biotransformation products in the fish tissue. RESULTS: Overall, 17 phase I diltiazem metabolites (including isomeric forms) were detected and tentatively identified using the MassFrontier spectral interpretation software. A semi-quantitative approach was used for organ-dependent comparison of the metabolite concentrations. CONCLUSIONS: These data increase our understanding about diltiazem and its metabolites in aquatic organisms, such as fish. These encompass desmethylation, desacetylation and hydroxylation as well as their combinations. This study represents the first report of the complex diltiazem phase I metabolic pathways in fish.
Keywords: chemické látky znečišťující vodu; Chromatography, Liquid; Muscles; molekulární struktura; Molecular Structure; Kidney; Water Pollutants, Chemical; blokátory kalciových kanálů; Mass Spectrometry; chromatografie kapalinová; ryby; Fishes; Animals; Calcium Channel Blockers; svaly; játra; Diltiazem; ledviny; zvířata; diltiazem; hmotnostní spektrometrie; Liver